2020
DOI: 10.3389/fnins.2020.00736
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Neural Arousal for Advertisements and Its Relationship With Advertising Success

Abstract: Abundant research has established the important role of ad-evoked feelings on consumers' reaction to advertising. However, measurement of feelings through explicit self-report is not without its limitations. The current study adds to previous work by showing a sophisticated way of first estimating how arousal is represented in the brain via an independent task (using EEG), and thereafter using this representation to measure arousal in response to advertisements. We then estimate the relationship between the id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 51 publications
(86 reference statements)
1
33
0
2
Order By: Relevance
“…For example, the EEG investigations of Vecchiato, et al [28] found that the activity in the right and left frontal alpha associated with pleasure and displeasure ads, respectively. Other the EEG studies, the findings of Eijlers, et al [29] showed that arousal is positively connected to prominent ads in the population and negatively to consumer attitude toward these ads. Cuesta-Cambra, et al [30] found that the visual activity of men is different from women, wherein the recall relies on the emotional value of ads and simplicity, while complex ads need more visual fixation; thereby, hard to remember.…”
Section: Neuromarketing Tools Used In Studying Consumers' Behavior To...mentioning
confidence: 99%
“…For example, the EEG investigations of Vecchiato, et al [28] found that the activity in the right and left frontal alpha associated with pleasure and displeasure ads, respectively. Other the EEG studies, the findings of Eijlers, et al [29] showed that arousal is positively connected to prominent ads in the population and negatively to consumer attitude toward these ads. Cuesta-Cambra, et al [30] found that the visual activity of men is different from women, wherein the recall relies on the emotional value of ads and simplicity, while complex ads need more visual fixation; thereby, hard to remember.…”
Section: Neuromarketing Tools Used In Studying Consumers' Behavior To...mentioning
confidence: 99%
“…A recent paper shows that an unequivocal interpretation of EEG measures is not always possible. Eijlers et al [ 33 ] measure arousal, resulting from looking at magazine advertisements (including food ads) using EEG, and conclude that their findings cannot be taken to show ad effectivity.…”
Section: Output Side: Measurement Technologiesmentioning
confidence: 99%
“…EEG is the most technology used in marketing practices before the release of the fMRI technique because of its less expensive and excellent temporal resolution (Alsharif et al, 2021d;Cruz et al, 2016;Lee et al, 2017;Telpaz et al, 2015). EEG is a non-invasive electrical technique, which is using electrodes placed on the consumer ' s scalp to measure the voltage changes of frequencies at scalp toward marketing stimuli in milliseconds (Cherubino et al, 2019;Davis, 2019;Eijlers et al, 2020;Kumar, 2015). According to the literature, EEG has five frequency bands such as delta (less than 4 hertz (Hz)), theta (4-7 Hz), alpha (8-15 Hz), beta (16-31 Hz), and gamma (larger than 32 Hz) (Wei et al, 2018).…”
Section: Electroencephalographymentioning
confidence: 99%
“…A number of studies have used EEG/ event-related potential (ERP) to measure the consumers ' behaviour toward marketing stimuli such as ads, products (Ciorciari et al, 2019;Eijlers et al, 2020;Samsuri et al, 2016a;Samsuri et al, 2016b). For example, the ERP and ET investigation to measure the attention level, pupil dilation, and fixation toward the display design of car advertisements.…”
Section: Electroencephalographymentioning
confidence: 99%
See 1 more Smart Citation